The Effectiveness of Regional Financial Management of Tolitoli Regency on Regional Development in 2018-2022 - Maskur, Maskur; Kasim, Fitri S. (Universitas Negeri Makassar, 2024)
This study aimed to assess the effectiveness and efficiency of regional financial management in Tolitoli Regency from 2018 to 2022. The research employed a descriptive quantitative approach, using effectiveness and efficiency ratio analyses based on secondary data obtained from the Regional Financial and Asset Management Agency (BPKAD). The findings reveal that the effectiveness of regional financial management for capital expenditures averaged 94.57% over the five-year period, which is classified as effective. However, the efficiency analysis showed an average of 94.65%, indicating that regional financial management was less efficient.